2011
DOI: 10.1161/hypertensionaha.111.171645
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Value of Home Blood Pressure

Abstract: Abstract-The maximum office systolic blood pressure (SBP) has been shown to be a strong predictor of cardiovascular events, independently of the mean SBP level. However, the clinical implications of maximum home SBP have never been reported. We investigated the association between the maximum home SBP and target organ damage (TOD). We assessed the left ventricular mass index (LVMI) and carotid intima-media thickness (IMT) using ultrasonography and the urinary albumin/creatinine ratio (UACR) as measures of TOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 37 publications
2
60
2
7
Order By: Relevance
“…Matsui and colleagues 23 showed that the maximum home SBP in untreated hypertensive patients was an independent determinant of the left ventricular mass index, carotid intima-media thickness, and UACR, indicating a possible predictive value of organ damage in hypertensive patients. Matsui and colleagues 22 also reported that the combination of olmesartan and azelnidipine reduced the SD of home SBP significantly more than the combination of olmesartan and a thiazide diuretic (À1.7 mm Hg vs À0.6 mm Hg; P=.01), and that the SD of home SBP was an independent determinant of aortic pulse wave velocity, indicative of arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsui and colleagues 23 showed that the maximum home SBP in untreated hypertensive patients was an independent determinant of the left ventricular mass index, carotid intima-media thickness, and UACR, indicating a possible predictive value of organ damage in hypertensive patients. Matsui and colleagues 22 also reported that the combination of olmesartan and azelnidipine reduced the SD of home SBP significantly more than the combination of olmesartan and a thiazide diuretic (À1.7 mm Hg vs À0.6 mm Hg; P=.01), and that the SD of home SBP was an independent determinant of aortic pulse wave velocity, indicative of arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…22 The home BP variability included the standard deviation (SD), the coefficient variation (CV), the maximum BP, and the morning minus evening BP. The SD and CV values were calculated based on the average daily BP (four readings daily) of five consecutive days, 22 the maximum BP defined as the highest average among the average duplicate morning BP and average duplicate evening BP values, 23 and the morning minus evening BP as the difference between the daily morning BP and the evening BP. Clinic BP was determined at the participating study sites to measure BP three times at each visit.…”
Section: Bp Measurementsmentioning
confidence: 99%
“…[1][2][3][4] However, there is growing evidence that central aortic arterial pressure may be better than peripheral arterial pressure in predicting cardiovascular events. [5][6][7] The gold standard for assessing central arterial pressure is direct measurement with an intra-aortic transducer.…”
Section: Introductionmentioning
confidence: 99%
“…The findings by Hoshide et al would be also consistent with a previous report from the same Kario's Laboratory showing a relatively weak association between home BP variability and albuminuria in a range of normo-to microalbuminuria, which is in contrast to the strong association that has been observed between home BP variability and cardiac hypertrophy in a cross-sectional study. 22 It is likely that the kidneys might not be affected by a transient increase in BP, as long as auto-regulatory mechanisms are functioning normally.…”
Section: T He Accumulated Results Of Clinical Trialsmentioning
confidence: 99%